1998
DOI: 10.3354/meps165137
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses to chemical cues of predation risk in a three-trophic-level Baltic Sea food chain

Abstract: Behavioural responses of 2 Baltic benthic crustaceans to chemical substances from predators were studied using infrared video-recording in the laboratory. This is the f~rst study of behavioural responses to species-specific chemical substances in a 3-trophic-level food chain. Exposure to chemical substances from a predatory fish, the short-horned sculpin Myoxocephalusscorp~us (L.), ca.used the isopod Saduria entomon (L.) to remain buried in the sediment most of the time and decreased its foraging success on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Donner et al (1987) reported field observations of increased swimming by Monoporeia affinis as feeding conditions deteriorated in late summer, suggesting that food shortage can also cause emigration from the sediment. M. affinis has been reported to swim away from unfavourable conditions, such as the presence of toxic contaminants (Lindström & Lindström 1980), low oxygen (Johansson 1997) and predator presence (Ejdung 1998, Sparrevik & Leonardsson 1999. Amphipod mortality during the experiment was mostly 9 to 27%, but reached over 40% in some treatments.…”
Section: Tests Of Density-dependence Of Growth Ratesmentioning
confidence: 96%
“…Donner et al (1987) reported field observations of increased swimming by Monoporeia affinis as feeding conditions deteriorated in late summer, suggesting that food shortage can also cause emigration from the sediment. M. affinis has been reported to swim away from unfavourable conditions, such as the presence of toxic contaminants (Lindström & Lindström 1980), low oxygen (Johansson 1997) and predator presence (Ejdung 1998, Sparrevik & Leonardsson 1999. Amphipod mortality during the experiment was mostly 9 to 27%, but reached over 40% in some treatments.…”
Section: Tests Of Density-dependence Of Growth Ratesmentioning
confidence: 96%
“…The crush-limited C. maenas can break the globular BS Macoma more easily than the flatter NS Macoma of similar size. Saduria entomon pry the shell valves apart (Ejdung 1998), and eat more of the flat and lightshelled NS Macoma. Crangon crangon swallow small M. balthica whole, pry open the shell or make a hole in the shell to extract the meat.…”
Section: Influence Of Prey Type and Prey Sizementioning
confidence: 99%
“…Ultimately many species have the means to recognise prey and predators, and to find and avoid them (Busdosh et al 1982, Ejdung 1998. Today animals disperse more rapidly to new areas through artificial waterways (Olenin & Leppäkoski 1999), are introduced by humans, or shift their distribution due to global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, single M. affinis had a higher radioactive uptake at C10.6 and C8.9 than did single P. femorata. Bioturbation (Cederwall 1979, Ejdung 1998) causes mixing of sediment particles in the upper 5 cm of the sediment (Lopez & Elmgren 1989), but is unlikely to have greatly mixed the sediment during our short-term experiments. The much lower uptake by P. femorata than by M. affinis in our experiments probably mainly represents evidence of surface feeding by subadult M. affinis as reported by Byrén et al (2002Byrén et al ( , 2006.…”
Section: Feedingmentioning
confidence: 99%